A preliminary taxonomic revision of the girii clade of South Asian Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) with the description of four new species from southern Maharashtra, India - Khandekar, Akshay; Gaikwad, Sunil M.; Thackeray, Tejas; Gangalmale, Satpal; Agarwal, Ishan (Zootaxa, 2024)
The girii clade is the most diverse clade of South Asian Cnemaspis in the Northern Western Ghats, including ten valid species. Recent collections of four divergent lineages from southern Maharashtra prompted us to examine the type material of all species in the girii clade, which led to the discovery of numerous errors and discrepancies in the literature. We take this opportunity to provide an updated and expanded morphological dataset including diagnoses and comparisons for all species of the girii clade and to build an almost complete species-level phylogeny including the first ND2 sequences of C. rajgadensis and C. uttaraghati, as well as the four new species described herein (but excluding C. fortis). We describe the four divergent mitochondrial lineages as new species using morphological data, and provide a key to species of the girii clade. Finally, we list some inconsistences in previous publications and data for the girii clade.